Lindy Roy : design series 1. - SFMOMA (San Francisco Museum of Modern Art) San Francisco; Alfred, Darrin; Benezra, Neal; Rosa, Joseph (San Francisco : SFMOMA (San Francisco Museum of Modern Art), 2003)
From an extreme skiing outpost in Alaska's Chugach Mountains to a sophisticated bar in Manhattan's Meatpacking District, the architecture of Lindy Roy combines fluid, folding forms with innovative responses to context and construction. The first publication devoted to her work, this catalogue - which accompanies an exhibition at the San Francisco Museum of Modern Art - marks the inaugural volume of the museum's new Design Series. An essay by Joseph Rosa, SFMOMA's Helen Hilton Raiser Curator of Architecture and Design, examines Roy's career to date, while texts by curatorial associate Darrin Alfred introduce nine of the architect's most significant projects, including a floating spa in Botswana's Okavango River Delta, an urban oasis in New York, a Houston residence designed for low-income communities, and the acclaimed Manhattan Vitra store.
geselect. bibliog. p. 48
Engels
Exhibition. ROY / design series 1. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2003-04-19. 2003-09-07
boek
Keywords: Roy, Lindy